Minimum time since death when the body has either reached or closely approximated equilibrium with ambient temperature. (December 2017) - Potente, S.; Kettner, M.; Verhoff, M.A.; Ishikawa, T.
Highlights: For cases with advanced cooling, a minimum time since death can be calculated with high probability. Charts, to be used as a simple graphical solution on the crime scene, are provided. One case example with detailed demonstration of method use is provided. Abstract: In temperature based death time estimation the construction of a death time interval using the conventional Nomogram method (NM) is not permissible for bodies in which rectal temperature ( T r ) has reached or closely approximated equilibrium with ambient temperature ( T a ). We provide a logic approach to compute a minimum time since death with high probability. We also provide a simple graphical solution to be used at the crime scene for preliminary estimation. Special attention is advised in regards to cases with T a > 23 °C as well as borderline cases. Proof by induction, application to test cases and one example of use are presented.